The Role of Private School Principle in Elementary Schools in Implementing Sekolah Penggerak - Minsih Minsih; Djalal Fuadi; Nanda Dwi Rohmah; Desti Rahayu; Maryam Nurlaila; Uslan Uslan; Ummi Tadzkiroh (STAI Hubbulwathan Duri, 2024)
The Sekolah Penggerak program is designed to enhance educational outcomes through structured support for principals, school supervisors, and teachers. This study aims to delineate the role of elementary school principals in fostering independent learning via enhanced learning processes within the Sekolah Penggerak framework. This qualitative study employed a phenomenological design to explore the perspectives of various stakeholders. Participants included school principals, eight teachers, two supervisors, and ten students. Data were collected through Focus Group Discussions (FGD), interviews, observations, and document analysis. The credibility of the data was ensured through dual triangulation methods: source and method triangulation. Data analysis followed a three-step inductive process: data reduction, data display, and verification, concluding with the synthesis of findings. Findings highlight two principal aspects of the Sekolah Penggerak program: (1) the pivotal role of the principal in enhancing the school ecosystem and (2) the principal’s leadership in activating school human resources as learning leaders. The study emphasizes the importance of In-House Training (IHT) activities, which are pivotal in increasing teacher capacity and include differentiation learning, mapping of children’s learning needs, reflective practices, and follow-up actions based on reflective outcomes. The results underscore the effectiveness of principal-led initiatives in supporting flexible and targeted learning enhancements. Through the strategic use of IHT, principals play a crucial role in both improving teaching practices and ensuring the active involvement of the entire learning community in achieving comprehensive educational goals. The Sekolah Penggerak program significantly contributes to the professional development of educators and the operational optimization of schools, affirming the crucial role of leadership in achieving educational excellence.